ChemInform Abstract: Metal Complexes of Curcumin — Synthetic Strategies, Structures and Medicinal Applications. Issue 36 (September 2015) - Wanninger, Simon; Lorenz, Volker; Subhan, Abdus; Edelmann, Frank T.
Abstract Review: 50 refs.